Mister Impossible - Stiefvater, Maggie, 1981- (Stiefvater, Maggie, 1981- Dreamer trilogy, 2021)
Ronan, Hennessy, and Bryde are dreamers; Ronan's dreams always seem to end in random destruction, using up the power of the ley lines he cannot even sense; Hennessy makes multiple copies of herself, dreaming them into reality in search of her own fragile identity, and Bryde dreams of power and reordering his companions and the world to his own specifications; their families and duplicates are the collateral damage of their dreams--and meanwhile they are hunted by the "Moderators," led by Carmen Farooq-Lane and the "Visionary" Liliana, determined to destroy the dreamers and save the world.